Impact assessment of the cleaner production (CP) and energy audit (EA) programs of DOST IV-A - Bagsit, Emelita P. (University of the Philippines Diliman, 2014)
Sustainable development is now the byword among the economists and environmentalists, which is somehow related to the current trends in population growth and industrialization. The impact of these observed trends includes irreversible damage to the environment that in some cases are life threatening. Pollutants are released at a rate faster than the earth can absorb, while natural resources are extracted and consumed at an unimaginable pace, putting the life of the future generations at risk. To abate the stress to the environment that human activities bring, a better way of producing products and services must be explored so that higher degree of productivity can be attained. This means efficient utilization or conversion of inputs such as raw materials and energy into high quality products, or inversely with minimal or nil wastage along the production chain. This concept of effective and efficient production process is better known as the "Cleaner Production." Cleaner Production (CP) is an environmental management approach whose goal is to improve the pro-environmental performance of products, processes and services by looking at the causes or sources of environmental problems rather than the symptoms. Unlike the traditional approach to pollution control wherein focus/action is "after-the-event" or reactive, commonly known as "end-of-pipe" action, CP is based on proactive or the "anticipate-and-prevent perspective". It is commonly applied in the production process through conservation of raw materials/resources, elimination of toxic raw materials, cutback on energy use, and reduction of wastes and emissions. The CP concepts can be applied throughout the life cycle of a product or service, starting from the initial design phase until the consumption and disposal stage. Strategies to implement CP may include one or combination of the following : improved housekeeping practices, process optimization, raw materials substitution, new technology and new product design. Related to the concept of Cleaner Production is the Energy Audit (EA), with some literatures stating that the former subsumes the latter. This is so because energy is technically considered as input in a production process. EA is a process that identifies where and how much energy is used in an existing facility, building or structure. The results then provide relevant information/inputs in the preparation and adoption of energy conservation measures (ECMs). Energy audits identify economically justified interventions to reduce the amount of energy input into the system without negatively affecting the output(s). Recognizing the importance of micro, small and medium enterprises (MSMEs) to the economic growth, DOST IV-A has been implementing programs and projects aimed to enhance operational efficiency and boost productivity and competitiveness of the 122, 562 MSMEs in the Region (NSO, 2005). However, literatures also cite that these MSMEs are the ones not complying with environmental standards set by regulatory bodies. This is so because of their lack of funds and the technical know-how to make their company compliant with the laws and policies of the government. In order to assist the MSMEs, DOST IV-A started the implementation of Cleaner Production (CP) in 2006 and Energy Audit in 2009, that promote technology innovations to improve productivity of the MSMEs by reducing wastes generation at the source and maximizing efficient use of energy. To demonstrate that DOST is really committed in providing technologies to MSMEs that would abate environmental problems, starting in 2012 CP and EA have already listed/considered as technology interventions under the Small Enterprise Technology Upgrading System (SETUP). Since the DOST IV-A is already investing so much resources (manpower and funds) to provide CP and EA assistance, it is but necessary to conduct a study to determine the impact of these interventions to the productivity and competitiveness of the MSMEs. This study focused on the assessment of the implementation of CP and EA in Region IV-A and the impacts they brought to the programs' beneficiaries. The success and failure factors of these two interventions were also analyzed. The study involved descriptive research method and qualitative approach in data collection and evaluation. The results of the study showed that CP and EA programs were highly important technical assistance of DOST IV-A. Based on the survey conducted, despite the challenges in implementing the programs, the beneficiaries of the programs recognized the benefits of implementing the CP and EA recommendations provided in the Assessment Reports. They have attributed or at least related the improvements in the efficiency of their production processes or general operations to the recommendations of the CP and EA teams. These ultimately led to outcomes such as savings and increased profit from the reduction of power consumption, less wastage of raw materials and products (less rejects), more efficient production processes and reduced costs of other utilities such as water. Compliance of the companies to government regulations was one of the important impacts of the assistance provided. Overall, it can be said that the CP and EA assessment results proved that these programs generally enhanced the productivity and competitiveness of the assisted companies.